2023
DOI: 10.1038/s41598-023-31601-z
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale effects of offshore wind farms on seabirds of high conservation concern

Abstract: The North Sea is a key area worldwide for the installation of offshore wind farms (OWFs). We analysed data from multiple sources to quantify the effects of OWFs on seabirds from the family Gaviidae (loons) in the German North Sea. The distribution and abundance of loons changed substantially from the period before to the period after OWF construction. Densities of loons were significantly reduced at distances of up to 9–12 km from the OWF footprints. Abundance declined by 94% within the OWF + 1 km zone and by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 60 publications
0
18
0
1
Order By: Relevance
“…Het is opvallend dat voor zeekoeten de gemiddelde dichtheid gestaag blijft toenemen als we steeds verder van het windpark af bewegen, over de gehele 0 tot 10 km. Voor deze interpretatie is wel een noodzakelijke aanname, dat zeekoeten het windpark op 10 km nog kunnen waarnemen: dit is wellicht aannemelijk op basis van een recente meta-analyse aan andere zeevogels (roodkeel-en parelduikers) in een nabijgelegen deel van de Noordzee (Garthe et al, 2023b). Zeekoeten uit de broedkolonie op Helgoland lieten vermijdingsafstanden zien tot 9 km van windparken in hun foerageergebied (Peschko et al, 2020).…”
Section: 321unclassified
“…Het is opvallend dat voor zeekoeten de gemiddelde dichtheid gestaag blijft toenemen als we steeds verder van het windpark af bewegen, over de gehele 0 tot 10 km. Voor deze interpretatie is wel een noodzakelijke aanname, dat zeekoeten het windpark op 10 km nog kunnen waarnemen: dit is wellicht aannemelijk op basis van een recente meta-analyse aan andere zeevogels (roodkeel-en parelduikers) in een nabijgelegen deel van de Noordzee (Garthe et al, 2023b). Zeekoeten uit de broedkolonie op Helgoland lieten vermijdingsafstanden zien tot 9 km van windparken in hun foerageergebied (Peschko et al, 2020).…”
Section: 321unclassified
“…However, the currently recognized total installed capacity of OWTs in China is approximately 27 GW [22], [23], which coincides with the median installed capacity determined from the dataset in this study, suggesting that this dataset has great potential for application in practical situations. For example, this dataset can be used to assess the impacts of offshore wind turbines on the ecological environment [49], [50], coastal and marine recreational tourism [51], migratory birds [52], and local socioeconomic [53] and fisheries development [54]. When conducting these studies, accurate and complete OWT datasets can reflect the true state of the problem and lead to more convincing research conclusions.…”
Section: E Potential Application Targets For Offshore Wind Turbine Da...mentioning
confidence: 99%
“…10 km (Mendel et al, 2019;Vilela et al, 2021;Garthe et al, 2023), while other species, such as large gulls (Larus sp. ), appear to show either no response or attraction to turbines (Welcker and Nehls, 2016;Johnston et al, 2022) and cormorants (Phalacrocorax carbo) are regularly reported to be attracted to turbines, or more pertinently to the structures and the opportunities for roosting provided (Canning et al, 2013;Leopold et al, 2013).…”
Section: Displacement Rates Found At Other Owfsmentioning
confidence: 99%